2019
DOI: 10.1111/twec.12842
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of unilateral trade policies EBA and AGOA on African beneficiaries' exports using matching econometrics

Abstract: The existing literature studying the impact of non‐reciprocal preferential trade agreements (NRPTAs) assumes implicitly NRPTAs are non‐randomly assigned without showing the evidence of that. Using a matching methodology, this paper investigates whether the “African Growth and Opportunity Act” (AGOA) and the “Everything But Arms” (EBA) unilateral trade concessions have had an impact, and in what magnitude, on the exports of African beneficiary countries in the light of the evidence of the non‐random nature (end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Alternatives of DiD such as propensity score matching (PSM) and synthetic control approach (SCA) should be explored in the context of export survival. Sorgho and Tharakan () have assessed the effect of AGOA and EBA using PSM approach, while Kassa and Coulibaly () have used SCA to study the effect of AGOA on eligible countries. With the availability of firm‐level data like the World Bank's Exporter Dynamics Database, more studies, besides Chacha and Edwards (), should approach this subject from a micro‐perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatives of DiD such as propensity score matching (PSM) and synthetic control approach (SCA) should be explored in the context of export survival. Sorgho and Tharakan () have assessed the effect of AGOA and EBA using PSM approach, while Kassa and Coulibaly () have used SCA to study the effect of AGOA on eligible countries. With the availability of firm‐level data like the World Bank's Exporter Dynamics Database, more studies, besides Chacha and Edwards (), should approach this subject from a micro‐perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Didia, Nica, and Yu (2015) also find evidence that AGOA has stimulated exports to the US, but find a disproportionate impact of crude oil exports from oil‐producing countries. Sorgho and Tharakan (2019) also find that AGOA has significantly increased beneficiaries’ exports to the US.…”
Section: The African Growth and Opportunity Actmentioning
confidence: 91%
“…Typically, this is due to domestic political instability. Sorgho and Tharakan (2019) show that political stability is a condition for AGOA eligibility. If political instability is associated with lower‐than‐normal growth rates and correlated with delayed/loss of eligibility for AGOA preferences, our measure of changes in AGOA eligibility might be inadvertently capturing these relationships.…”
Section: Robustness Checksmentioning
confidence: 99%
“…The study by Sorgho and Tharakan (2019) applied the Logit regression and the Propensity Score Matching (PSM), shows that though, AGOA has a positive impact on the economy, however, one of the reasons, while most African countries did not experience a positive impact of AGOA trade policy, is as a result of an institutional framework. The study found Note: The HS Codes H0 to H4 is the classification of goods as indicated by the "Harmonised System (HS)" which was created and administered by the Brussels-based World Customs Organisation (WCO).…”
Section: Evaluating Nigeria's Pre-and Post-agoa Participationmentioning
confidence: 99%
“…The comparatively satisfactory economic performance, discovery of various natural resources, and conducive political environment have provoked the interest of many advanced countries including the USA, the European Union (EU), China, Russia, India, Japan, Brazil, among others to initiate trade relations with several African countries ( Davies and Nilsson, 2020 ; Hurreeram and Little, 2004 ; Mahabir et al, 2020 ; Sorgho and Tharakan, 2019 ; Thompson, 2004 ). The establishment of multilateral frameworks in Africa countries has become a significant feature in international relations among major economic powers and various regional economic communities as they strive to deepen their economic cooperation and address the challenges faced in a globalised world ( Davis and Nilsson, 2020 ; Mahabir et al, 2020 ; Musah et al, 2020 ; Osabuohien et al, 2019 ; Salau, 2018 ).…”
Section: Introductionmentioning
confidence: 99%